Serum uric acid levels in acute myocardial infarction - V., Padma; Banupriya, Amogh (International Journal of Advances in Medicine, 2017)
Background: Higher uric acid is a negative prognostic factor in patients with mild to severe heart failure. Studies have shown that there is a close correlation between serum uric acid concentration and Killip classification in patients of acute myocardial infarction and uric acid levels are higher in patients with higher Killips class. Methods: We studied 100 patients with acute myocardial infarction and compared with 100 controls. Serum uric acid level was measured on day 0, 3 and 7 of MI and results were analysed. Results: Average uric acid level in male cases was 5.6 and female cases was 5.2, male controls were 4.2 and female controls was 3.6. Females had a higher mortality when compared with male patients. One female died due to MI on day 0, one male and two females died on day 3 and four males and four females died on day 7. All patients who died had higher uric acid levels. Conclusions: Serum uric acid levels are higher in patients of acute myocardial infarction as compared to normal healthy persons. Serum uric levels increases in patients with higher Killip class. Combination of Killip class and serum uric acid level after acute myocardial infarction is a good predictor of mortality after acute myocardial infarction.